THE KRIS/STABOR WITHIN ROMA COMMUNITIES FROM EASTERN AND SOUTHERN ROMANIA. WHAT SOURCES FOR THE LEGITIMACY OF ‟KRISNITORI” AND FOR THE PERPETUATION OF ‟KRIS”? / LE KRIS DANS LES COMMUNAUTES ROM DE SUD-EST DE LA ROUMANIE. QUELLES SONT LES SOURCES POUR LA L - HERȚA, Laura M. (Studia Universitatis Babes-Bolyai Studia Europaea, 2016)
This study aims at presenting and analysing pivotal cultural features and values which structure the Roma court (kris/stabor) in Romania. The main hypothesis of this article is centred on the idea that the Roma court (kris/stabor) functions as both constitutive and regulative normative body within Roma communities, hence ensuring the legitimacy of Roma judges (krisnitori), the survival and the perpetuation of the community itself. The research questions meant to structure this article are: Why do Roma people prefer the Roma court (kris/stabor) and not the national court in Romania? What are the sources for the legitimacy of the Roma court and Roma judges? What are the relations between the Roma court and the activity of the juridical, state apparatus? How is the Roma judgement perpetuated?